2022
DOI: 10.1021/acssuschemeng.2c04493
|View full text |Cite
|
Sign up to set email alerts
|

Pillar[5]arene-Based Co(III)-Loaded Covalent Organic Polymer for Efficient CO2 Cycloaddition under Mild Conditions

Abstract: Generating promising materials for the conversion of CO2 to valuable industrial products under mild conditions is important for both ameliorating the greenhouse effect and sustainable development. Pillar[5]arene-incorporated materials have recently emerged as building frameworks to construct versatile functional polymeric materials. Herein, we demonstrate that highly efficient fixation of CO2 to cyclic carbonates can be achieved by employing a novel pillar[5]arene-based Co(III)-loaded covalent organic polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…In addition, according to the Clausius–Clapeyron equation, the isosteric adsorption heat ( Q st ) of Zn-HUT4 for CO 2 was calculated (Figure f). Zn-HUT4 had high Q st value (36.1 kJ/mol) at low loading, which could be attributed to the effective capture of CO 2 by the rich polar groups containing N and O atoms on the HUT4 skeleton. …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, according to the Clausius–Clapeyron equation, the isosteric adsorption heat ( Q st ) of Zn-HUT4 for CO 2 was calculated (Figure f). Zn-HUT4 had high Q st value (36.1 kJ/mol) at low loading, which could be attributed to the effective capture of CO 2 by the rich polar groups containing N and O atoms on the HUT4 skeleton. …”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, we studied the catalytic performance of the catalyst under ambient conditions (Table 2, Entry 20). Owing to the mild reaction conditions, we used 5 mL of PO, 300 mg of Zn-HUT4 (0.414 mmol Zn), and 528 mg (1.62 mmol) of TBAB at 25 °C and 1 bar of CO 2 for 48 h. It was found that the conversion of PO was only 25.7%, the selectivity of PC was only 67.1%, and the remaining 32.9% of the product was polycarbonate without polyether segments (Figure S10), indicating that the catalytic activity of Zn-HUT4 under ambient conditions was not satisfactory, 30,36,38 so we did not further study it. In order to study the recyclability of the Zn-HUT4 catalyst, five cycles of catalytic experiments were carried out (Figure 4).…”
Section: Catalyticalmentioning
confidence: 99%
“…), which seriously have threatened the survival of human beings. Consequently, the capture and utilization of CO 2 has received unprecedented attention in recent years. , Among them, CO 2 cycloaddition reaction holds great promise because of its 100% atomic utilization efficiency and subsequent highly valued cyclic carbonate products. However, nowadays, industrial routes mainly rely on the traditional TBAB, KI, and other halogen anion nucleophilic reagent homogeneous catalysts, which suffer from low conversion, harsh reaction conditions, and expensive equipment investment . Part of novel catalytic technology based on ionic liquid-based multifunctional homogeneous catalysts is still confronted with high reaction pressure, unsatisfied catalytic efficiency, and homogeneous separation problem. As a result, developing highly efficient heterogeneous catalysts that can work under mild conditions holds great promise for technological upgrading of CO 2 cycloaddition.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the capture and utilization of CO 2 has received unprecedented attention in recent years. 1,2 Among them, CO 2 cycloaddition reaction holds great promise because of its 100% atomic utilization efficiency and subsequent highly valued cyclic carbonate products. 3−5 However, nowadays, industrial routes mainly rely on the traditional TBAB, KI, and other halogen anion nucleophilic reagent homogeneous catalysts, 6 which suffer from low conversion, harsh reaction conditions, and expensive equipment investment.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic polymers (COPs) are a kind of attractive materials holding great application potential in the fields of environmental remediation and molecular or metal ion sieving. 22,23 They are constructed from repeating designable building blocks, which endows them with high structural modularity and abundant functionality. Furthermore, most COPs exhibit excellent hydrolytic stability even under highly acidic conditions because they are connected totally by stable covalent bonds.…”
Section: Introductionmentioning
confidence: 99%